Incidence and risk factors of ischemic stroke in patients with cancer-associated venous thromboembolism: from the Contemporary Management and Outcomes in Patients With Venous Thromboembolism Registry-2 - Toru Sato; Yoshito Ogihara; Yugo Yamashita; Takeshi Morimoto; Ryuki Chatani; Kazuhisa Kaneda; Yuji Nishimoto; Nobutaka Ikeda; Yohei Kobayashi; Satoshi Ikeda; Kitae Kim; Moriaki Inoko; et al. (Research and Practice in Thrombosis and Haemostasis)
Background: Ischemic stroke is a serious complication in patients with cancer-associated venous thromboembolism (CAVTE), although data remain scarce in the direct oral anticoagulant era. Objectives: This study aimed to investigate the incidence and identify predictive risk factors of ischemic stroke in patients with CAVTE. Methods: From the Contemporary Management and Outcomes in Patients With Venous Thromboembolism Registry-2 enrolling 5197 venous thromboembolism (VTE) patients across 31 centers in Japan between January 2015 and August 2020, we selected 1507 patients with active cancer. We calculated the cumulative incidence function of ischemic stroke accounting for the competing risk of death and investigated risk factors for ischemic stroke in a subdistribution hazard model of multivariable analysis. Results: During a median follow-up period of 1020 days, 71 patients (4.7%) developed ischemic stroke, and the cumulative incidence of ischemic stroke was 4.0% at 1 year and 4.7% at 3 years. Independent risk factors of ischemic stroke included pancreatic cancer (hazard ratio [HR], 4.24; 95% CI, 2.13-8.43), ovarian cancer (HR, 2.82; 95% CI, 1.31-6.08), lung cancer (HR, 2.35; 95% CI, 1.20-4.57), dyslipidemia (HR, 1.76; 95% CI, 1.01-3.09), metastasis (HR, 1.70; 95% CI, 1.02-2.82), higher D-dimer at VTE diagnosis (HR, 1.09; 95% CI, 1.04-1.14), and younger age (HR, 0.84; 95% CI, 0.71-0.999). Conclusion: In this large VTE registry in the direct oral anticoagulant era, the cumulative incidence of ischemic stroke was 4.0% at 1 year and 4.7% at 3 years in patients with CAVTE, and several independent risk factors of ischemic stroke were identified, including pancreatic cancer, ovarian cancer, lung cancer, dyslipidemia, metastasis, higher D-dimer at VTE diagnosis, and younger age.